Work Coaching and Motivation to Improve Employee Productivity in a Public Sector Institution - Rohmad Rohmad; Musmuliadi Musmuliadi; Agustinus Djue (PT. Global Research Collaboration, 2026)
Purpose – This study aims to examine the role of work coaching and motivation in improving employee productivity in a public sector institution. Design/Method/Approach – A qualitative approach with a descriptive design was employed. Data were collected through in-depth interviews, observations, and documentation. The informants included institutional leaders, division heads, section heads, and employees. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Findings – The findings reveal that work coaching is implemented through training programs, technical guidance, direct instruction, and leadership supervision. Employee motivation is influenced by the work environment, interpersonal relationships, leadership support, and recognition of performance. Overall, employee productivity is relatively good; however, several challenges remain, including limited work facilities and unequal access to training opportunities. Implications/Limitations – This study highlights the importance of strengthening employee coaching programs and motivational strategies through leadership support, reward systems, and improved work facilities. The findings are limited to a single public sector institution, which may restrict broader generalization. Originality/Value – This study provides contextual insight into the relationship between work coaching, motivation, and employee productivity in a public sector organization.